Extreme reduction in body size and reproductive output associated with sandy substrates in two anuran species - Marangoni, Federico (2008)
Geographic variation in body size and reproductive traits has been reported in a wide range of organisms, including amphibians. Most studies have focused on latitudinal and/or altitudinal variation where differences in temperature and duration of the growing season are the main causes for population divergence. We describe a steep variation in body size and reproductive traits in two anuran species in southwestern Spain, associated with changes in the geological substrate. Pelobates cultripes and Bufo calamita (= Epidalea calamita) drastically reduced their size (a 71.6% and 76.1% reduction in body mass for P. cultripes and B. calamita, respectively) in just about 60 km. This extreme size reduction was more pronounced at the boundary between two different geological substrates (hercinic and sandy soil). Mean clutch mass, egg size, and clutch size were all smaller in B. calamita populations in the sandy environment. Likewise, clutch mass and egg size were both smaller in sandy P. cultripes populations. We observed a negative correlation between size-adjusted fecundity and egg size for both species, suggesting the existence of a reproductive trade-off that could explain the differences in reproductive allocation between populations and species. In P. cultripes, small-bodied populations had relatively higher fecundities and smaller eggs than large-bodied ones, whereas in B. calamita populations from the sandy area we found both populations with high fecundity and small eggs, and populations with low fecundity and large eggs. Common environmental effects associated with the sandy substrate produce a similar reduction in size in both toad species. © 2008 Koninklijke Brill NV, Leiden.